OLEIC ACID LEVELS IN BREASTFEEDING (0-24 MONTHS) AND DETERMINANTS THAT AFFECT IT: LITERATURE REVIEW - Nursari Abdul Syukur,, Citrakesumasari, Anwar Mallongi, Syamsiar S.Russeng, (Chelonian Research Foundation, 2024)
This paper presents the results of a literature review on Oleic Acid Levels in Breast Milk and its Determinants. The search refers to the Preferred Reporting Items for Systematic Reviews (PRISMA) guidelines. The literature in this study is accessed from scientific article sites that have open access, such as Hurzing Publish or perish, with a selection of Scopus-indexed journals obtaining 200 articles, indexed Google Scholar 1154 articles, Cochrane Library 67 articles, PUBMED 97 articles, CINAHL 110 articles, MEDLINE 47 articles and after going through the article extraction process, followed by the extraction technique, The strategy used is the PICOS framework of this article then in the related further analysis title and abstract and obtained 16 eligible articles. Various forms of intervention have been carried out. To increase exclusive breastfeeding. Expanding the knowledge of mothers and families about the content of breast milk, especially oleic acid, can prevent cancer. Several articles found that providing knowledge about the content of breast milk, such as oleic acid, can increase breastfeeding exclusively.